A descent extension of the Dai - Yuan conjugate gradient technique - Basim Abbas Hassan; Zeyad M. Abdullah; Hawraz N. Jabbar (Institute of Advanced Engineering and Science, 2019)
Based on Dai - Yuan technique, a new extension method was proposed. In contrary to the CG classical method, this proposed method employs a coefficient that has an important role in constructing the new formula with less computational efforts. This proposed method was found to be efficient on the basis of theory analysis and numerical results.